Pelatihan Digital dengan Aplikasi Canva Sebagai Penunjang Kegiatan Promosi di TPQ Bina Ummah - Mohammad Badrul; Laila Septiana; Cahyani Budihartanti; Yumi Novita Dewi (Abditeknika Jurnal Pengabdian Masyarakat, 2023)
TPQ Bina Ummah is a religious educational institution, especially Islamic religion and other religious materials. Every activity carried out by TPQ Bina Ummah needs to be documented as a means of information to parents or the community. Information on activities carried out at TPQ Bina Ummah so far has only been conveyed in the whatsapp group of parents of students or fellow staff and educators by sending photos of activities by adding words as information. This information is often unreadable because it is covered by comments from fellow members in the WhatsApp group. This very narrow range of information which only contains members of the group is one of the obstacles to information that should be able to reach the community, especially the people within the TPQ Bina Ummah environment. Therefore, it is necessary to understand how to process data to be more informative, especially in terms of design. The training conducted with Canva as a support for promotional and marketing activities at TPQ Bina Ummah aims to support the competence of staff and educators in the field of digital marketing, especially in processing activity data into more informative information. Based on the results of the questionnaire regarding the evaluation of Community Service activities that had been carried out, the participants gave very good ratings. As many as 72% of participants stated that this activity was very useful and 60% of the training participants stated that they were very interested in participating again in the next training.